1996
DOI: 10.1177/002246699603000304
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self-Management in an Individual with Mental Retardation

Abstract: The development of self-management skills in an individual with Down syndrome is explored through ethnographic methodology, including interviews, observations, and document reviews. The culture of the case subject was explored to determine how her home life, family (including her twin brother), schooling, and community experiences have contributed to her abilities to selfregulate. Development of her self-monitoring skills was investigated through the memories of the adults who knew her currently and in the pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For example, parents can model concrete advocacy skills and teach their children coping techniques and adaptability as together they face the challenges of the child's disability. In studying the development of self-management in an individual with mental retardation, Richardson, Kline, and Huber (1996) found that the young woman's mother had been a primary influence on her development of self-reliance. In contrast, professionals in counseling psychology have noted a trend in U.S. society-called parentification-in which busy parents abdicate their caregiving role, leaving children to try to parent themselves (Chase, 1998).…”
Section: Pitfall 3: Neglecting Collaboration With Familiesmentioning
confidence: 99%
“…For example, parents can model concrete advocacy skills and teach their children coping techniques and adaptability as together they face the challenges of the child's disability. In studying the development of self-management in an individual with mental retardation, Richardson, Kline, and Huber (1996) found that the young woman's mother had been a primary influence on her development of self-reliance. In contrast, professionals in counseling psychology have noted a trend in U.S. society-called parentification-in which busy parents abdicate their caregiving role, leaving children to try to parent themselves (Chase, 1998).…”
Section: Pitfall 3: Neglecting Collaboration With Familiesmentioning
confidence: 99%